PENGEMBANGAN MODEL KONSELING KELUARGA SAKINAH UNTUK MENCEGAH PENYALAHGUNAAN NARKOBA PADA REMAJA - Manah Rasmanah (Wardah, 2018)
Abstract This study aims to (1) obtain an overview of the implementation of counseling for sakinah families, (2) obtain a description of the level of drug abuse trends in first-degree students, (3) produce a model of counseling for sakinah families to prevent drug abuse in adolescents, (4) know the effectiveness of the model . This study uses the Research and Development (R & D) method. Research and Development steps: (1) preparation of model development, (2) formulating a hypothetical model, (3) hypothetical model feasibility test, (4) improvement of hypothetical models, (5) testing of the effectiveness of limited models, methods of collecting data through interviews , observation and dissemination of the scale of drug abuse trends. The research population was counseling experts in Palembang and the first level students of the Islamic Counseling Guidance Study Program at the Raden Fatah UIN Faculty of Palembang. The sampling technique was purposive sampling. The results showed that the level of tendency of first-year narcotics abuse in high criteria was 4 students or 4.48%, the medium criteria were 20 students or 17.39%, criteria were less than 30 students or 26.09%, low criteria 61 students or 53.04%. There was a significant difference in the trend of non-drug abuse in first-year students after their parents attended a sakinah family counseling of 0.005 <0.5. Keywords : sakinah family counseling, drug abuse, adolescents